Multimodal approach to the international transit transport - Bazaras, Darius; Palšaitis, Ramūnas (Transport, 2003)
In the article not only the problems of multi-modal and inter-modal conveyances in Lithuania and the concept of transit and the transit system stimulating factors are analysed, but also the modelling of transit transport and the flows of the loads are given. The main part of the article comes to the analysis of resent situation of Lithuania. In this part the place of transport sector in the market of transit services is analysed and the transit profit for Lithuanian economy is evaluated. The conclusions and proposals are given at the end of the article. First Published Online: 19 Dec 2011